Observation of a blocking to channeling transition for MeV protons at stacking faults in silicon. - King, P; Breese, M; Smulders, P; Wilshaw, P; Grime, G (1995)
Images of stacking faults in silicon have been produced using transmitted, channeled protons. They reveal that when the proton beam angle to the (111) channeling planes is slightly reater than the channeling critical angle, the mean energy loss of protons passing through a stacking fault is less than that of protons passing through virgin crystal. We interpret this as being caused by the conversion of the proton trajectories from blocked to channeled owing to the lattice translation at the stacking faults. Computer simulations are shown which verify this unexpected phenomenon.